2017
DOI: 10.1371/journal.pone.0175171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two prognostic scores (BSI and FACED) in a Spanish cohort of adult patients with bronchiectasis and improvement of the FACED predictive capacity for exacerbations

Abstract: Bronchiectasis (BE) is a chronic and heterogeneous respiratory disease that requires a multidimensional scoring system to properly assess severity. The aim of this study was to compare the severity stratification by 2 validated scores (BSI and FACED) in a BE cohort and to determine their predictive capacity for exacerbations and hospitalizations. Moreover, we proposed a modified version of FACED which was created to better predict the risk of exacerbations in clinical practice. We performed a prospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
2
24
0
1
Order By: Relevance
“…(7) Several recent comparisons between the BSI and the similar FACED score found that FACED did not accurately predict future risk of exacerbations suggesting that it was not a valid predictor of severity of disease. (16,32) The major difference between the scores is that BSI incorporates history of exacerbations which are not included in FACED. (16,32) Modification of the FACED to include a past history of exacerbations has been shown to improve its prediction of exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Several recent comparisons between the BSI and the similar FACED score found that FACED did not accurately predict future risk of exacerbations suggesting that it was not a valid predictor of severity of disease. (16,32) The major difference between the scores is that BSI incorporates history of exacerbations which are not included in FACED. (16,32) Modification of the FACED to include a past history of exacerbations has been shown to improve its prediction of exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Por ello, es una escala que debería aplicarse de forma sistemática para los pacientes con IDCV y bronquiectasias. 6,18,19…”
Section: Discussionunclassified
“…It is also just as difficult to establish the specific parameters that must be used to define an exacerbation; parameters that are usually grouped as symptoms and/or factors involving the use of health resources or a need for treatment. Nevertheless, in the case of bronchiectasis, and other respiratory diseases, exacerbations ( particularly severe exacerbations) have a demonstrable negative impact on a patient's prognosis [1][2][3][4] and entail great expense [5,6], and so their identification, and therefore their definition, is crucial to any early detection and treatment. Ideally, such a definition should present a perfect diagnostic value and, as regards bronchiectasis, be based on reproducible objective measurements linked to inflammation/bronchial infection (biomarkers) and their consequences (acute clinical symptoms).…”
Section: @Erspublicationsmentioning
confidence: 99%
“…One important point, fully explained by the authors, is that this is a definition for use in research, as it may have a high specificity (little probability of identifying exacerbations that are not in fact exacerbations). This leads to selection bias towards more severe exacerbations, although in a research context it is preferable to err in this direction as it is the severe forms that most seem to affect a patient's prognosis [1][2][3][4], and they are thus the most appropriate target or inclusion criterion for clinical studies. However, the definition does incorporate a number of symptomatic elements, and the need to change treatment (in this case, to prescribe antibiotics), which may contribute towards a better balance between sensitivity and specificity.…”
Section: @Erspublicationsmentioning
confidence: 99%